GT198 Is a Target of Oncology Drugs and Anticancer Herbs - Pang, Junfeng; Gao, Jie; Zhang, Liyong; Mivechi, Nahid F.; Ko, Lan (Frontiers in Oral Health, 2021)
Tumor angiogenesis is a hallmark of cancer. Therapeutic drug inhibitors targeting angiogenesis are clinically effective. We have previously identified GT198 (gene symbol PSMC3IP, also known as Hop2) as an oncoprotein that induces tumor angiogenesis in human cancers, including oral cancer. In this study, we show that GT198 protein is a direct drug target of more than a dozen oncology drugs and several clinically successful anticancer herbs. GT198 is a DNA repair protein that binds to DNA. Using an in vitro DNA-binding assay, we tested the approved oncology drugs set VII from NCI containing 129 oncology drugs. Identified GT198 inhibitors include but are not limited to mitoxantrone, doxorubicin, paclitaxel, etoposide, dactinomycin, and imatinib. Paclitaxel and etoposide have higher binding affinities, whereas doxorubicin has higher binding efficacy due to competitive inhibition. GT198 shares protein sequence homology with DNA topoisomerases, which are known drug targets, so that GT198 is likely a new drug target previously unrecognized. To seek more powerful GT198 inhibitors, we further tested several anticancer herbal extracts. The positive anticancer herbs with high affinity and high efficacy are all clinical successful ones, including allspice from Jamaica, Gleditsia sinensis or honey locust from China, and BIRM from Ecuador. Partial purification of allspice using organic chemical approach demonstrated great feasibility of natural product purification, when the activity is monitored by the in vitro DNA-binding assay using GT198 as target. Together, our study reveals GT198 as a new targeting mechanism for existing oncology drugs. The study also delivers an excellent drug target suitable for compound identification and natural product purification. In particular, this study opens an opportunity to rapidly identify drugs with high efficacy and low toxicity from nature.